Analisis Komparatif Faktor Pengeluaran Belanja Bulanan Antara Konsumen Laki-Laki Dan Perempuan - Dini Hanifah; Putri Dina Amelia; Rizqy Hizbullah Ziyaulhaq; Roudhotul Hayati Nurislami; Mia Lasmi Wardiyah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to evaluate the existence of significant differences in the level of monthly shopping expenditure between male and female consumers. The background of this study is based on the assumption that consumption behavior is influenced by various social, psychological, and economic factors, including potential differences in behavior based on gender. The methodology used is a comparative quantitative approach with data collection through questionnaires from 42 respondents selected using purposive sampling techniques. The instruments used have undergone validity and reliability tests with results that meet the criteria. Data were analyzed using a normality test and continued with the Mann-Whitney test to determine differences in spending between respondent groups based on gender. The results of the analysis showed that there was no statistically significant difference between male and female monthly spending, although descriptively, the average ranking of male spending was higher. This finding indicates that gender is not the main factor influencing the size of monthly consumption expenditure. Therefore, marketing strategies and economic policies need to pay attention to consumer characteristics more holistically, not solely based on gender.